Consumer Protection Against Overclaims of SS Skin Skincare Product Composition, Ibnu Taimiyah's Perspective - Hasibuan, Siti Erika Jumintan; Tarigan, Tetty Marlina (IHSA Institute, 2025)
This study examines consumer protection against overclaim practices in the marketing of SKINCARE SS Skin products from Ibn Taimiyah's perspective. Overclaim practices, such as excessive claims regarding the percentage of content or the use of prohibited claims, have the potential to harm consumers both materially and immaterially. This study uses a normative method with a statutory and conceptual regulatory approach. Data were collected through document studies and interviews, then analyzed descriptively qualitatively. The results of the Ibn Taimiyah perspective study, this practice is included in the category of gharar (fraud) and provides false information, which is contrary to the principle of justice in transactions, indicating that overclaim practices in the marketing of SKINCARE SS Skin products violate consumer rights and the obligations of business actors as regulated in Article 3 paragraph (2) of BPOM Regulation Number 3 of 2022, Article 3 of BPOM Regulation Number 32 of 2021, and the Consumer Protection Law. Losses caused by overclaim practices include material losses, such as money spent on unsuitable products, as well as immaterial losses, such as skin health problems and emotional disappointment. Therefore, business actors are required to be responsible for consumer losses in accordance with Articles 19-20 of the Consumer Protection Act, Articles 1365-1367 of the Civil Code, and the provisions of sanctions in BPOM Regulation Number 3 of 2022